2018
DOI: 10.1016/j.dnarep.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for damage recognition and verification by XPC-RAD23B and TFIIH in nucleotide excision repair

Abstract: Global genome nucleotide excision repair (GG-NER) is the main pathway for the removal of bulky lesions from DNA and is characterized by an extraordinarily wide substrate specificity. Remarkably, the efficiency of lesion removal varies dramatically and certain lesions escape repair altogether and are therefore associated with high levels of mutagenicity. Central to the multistep mechanism of damage recognition in NER is the sensing of lesion-induced thermodynamic and structural alterations of DNA by the XPC-RAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 115 publications
(144 reference statements)
2
67
0
3
Order By: Relevance
“…Previously, it was shown that tethering DDB2 to chromatin recruits XPC but never TFIIH, whereas tethering XPC recruits TFIIH but never DDB2, implying that DDB2 and TFIIH associate with XPC on DNA damage in a mutually exclusive manner 63 . Furthermore, the superimposition of the crystal structures of DDB2 and yeast XPC/Rad4 bound to DNA indicates that the two proteins cannot stably bind the same lesion simultaneously, as both interact with the DNA minor groove around the lesion 10,11,15,56 . However, lesion-bound CRL4 DDB2 is required for XPC ubiquitylation 23 , arguing that DDB2 and XPC should-temporarily-coexist, prior to the handover of the damage to the XPC-TFIIH verification complex.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that tethering DDB2 to chromatin recruits XPC but never TFIIH, whereas tethering XPC recruits TFIIH but never DDB2, implying that DDB2 and TFIIH associate with XPC on DNA damage in a mutually exclusive manner 63 . Furthermore, the superimposition of the crystal structures of DDB2 and yeast XPC/Rad4 bound to DNA indicates that the two proteins cannot stably bind the same lesion simultaneously, as both interact with the DNA minor groove around the lesion 10,11,15,56 . However, lesion-bound CRL4 DDB2 is required for XPC ubiquitylation 23 , arguing that DDB2 and XPC should-temporarily-coexist, prior to the handover of the damage to the XPC-TFIIH verification complex.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 UV-DDB is believed to hand off cyclobutane pyrimidine dimer (CPD) lesions to XPC. 2 This essential lesion recognition role of XPC has been well established by experimental studies, which have shown that XPC binding is required for the subsequent binding of the TFIIH complex. 1,1416 The XPD helicase in TFIIH verifies the lesion.…”
Section: Introductionmentioning
confidence: 92%
“…In TC-NER, recognition is accomplished by a stalled RNA polymerase II. In GG-NER, the current focus, recognition is carried out by the XPC-RAD23B complex, 2 aided in cells by centrin 2 11 and UV-DDB for UV photo lesions. 12,13 UV-DDB is believed to hand off cyclobutane pyrimidine dimer (CPD) lesions to XPC.…”
Section: Introductionmentioning
confidence: 99%
“…Positive Pearson coefficients were found in several genes, including XAB2 metaphase delay 23 , UVRAG (pro autophagy and NOTCH positive regulator) 24 , and SFPQ, a multifunctional pro DNA repair gene 25 , which is also involved in the regulation of L1 retrotransposons and proliferation 26 . Two other genes in the DNA repair hallmark having positive Pearson coefficients include RAD23B (nucleotide excision repair) 27 , and ATXN3 (represses the tumor suppressor PTEN), which is associated with tumor proliferation in gastric, lung, and testicular cancers 28,29 .…”
Section: Predicted Gene Expression and Direct Effect Model Hazardmentioning
confidence: 99%